Modeling Interfacial Glass‐Water Reactions: Recent Advances and Current Limitations. (12th July 2014) - Pierce, Eric M.; Frugier, Pierre; Criscenti, Louise J.; Kwon, Kideok D.; Kerisit, Sebastien N.
<x xml:space="preserve">Abstract</x> Describing the reactions that occur at the glass–water interface and control the development of the altered layer constitutes one of the main scientific challenges impeding existing models from providing accurate radionuclide release estimates. Radionuclide release estimates are a critical component of the safety basis for geologic repositories. The altered layer (i.e., amorphous hydrated surface layer and crystalline reaction products) represents a complex region, both physically and chemically, sandwiched between two distinct boundaries—pristine glass surface at the inner most interface and aqueous solution at the outer most interface. Computational models, spanning different length and timescales, are currently being developed to improve our understanding of this complex and dynamic process with the goal of accurately describing the mesoscale changes that occur as the system evolves. These modeling approaches include geochemical simulations (i.e., classical reaction path simulations and glass reactivity in allowance for alteration layer simulations), Monte Carlo simulations, and molecular dynamics methods. Discussed in this manuscript are the advances and limitations of each modeling approach placed in the context of the glass–water reaction and how collectively these approaches provide insights into the mechanisms that control the formation and evolution of altered layers. New results are presented as examples of each approach.